Function and Regulation of IL-36 Signaling in Inflammatory Diseases and Cancer Development - Queen, Dawn; Ediriweera, Chathumadavi; Liu, Liang (Frontiers in Cell and Developmental Biology, 2019)
The IL-36 subfamily of cytokines belongs to the IL-1 superfamily and consist of three pro-inflammatory agonists IL-36α, IL-36β, IL-36γ, and an IL-36 receptor (IL-36R) antagonist, IL-36Ra. These IL-36 cytokines function through a common receptor to modulate innate and adaptive immune responses. IL-36 cytokines are expressed as inactive precursors and require proteolytic processing to become fully active. Upon binding to the IL-36R, IL-36 agonists augment the expression and production of inflammatory cytokines via activating signaling pathways. IL-36 is mainly expressed in epidermal, bronchial, and intestinal epithelial cells that form the barrier structures of the body and regulates the balance between pro-inflammatory and anti-inflammatory cytokine production at these tissue sites. Dysregulation of IL-36 signaling is a major etiological factor in the development of autoimmune and inflammatory diseases. Besides its critical role in inflammatory skin diseases such as psoriasis, emerging evidence suggests that aberrant IL-36 activities also promote inflammatory diseases in the lung, kidneys, and intestines, underscoring the potential of IL-36 as a therapeutic target for common inflammatory diseases. With the growing appreciation of the link between inflammation and cancer, there is an emerging interest in understanding the role of IL-36 signaling in cancer development. In this comprehensive review, we summarize current knowledge regarding the expression, activation, regulatory mechanisms, and biological functions of IL-36 signaling in immunity, inflammatory diseases, and cancer development.